Sugar maple tree canopies as reservoirs for arthropod functional diversity in forest patches across a fragmented agricultural landscape in southern Quebec, Canada. Issue 1 (2nd April 2016) - Maguire, Dorothy Y.; Bennett, Elena M.; Buddle, Christopher M.
ABSTRACT: Forest fragments and their tree canopies may act as important reservoirs for biodiversity, but their role in supporting diversity is poorly understood in the context of their spatial arrangement. We examine the influence of landscape configuration and location within forest patches (e.g. canopy, edge or patch interior) on patterns of arthropod biodiversity associated with sugar maple trees across an agricultural landscape in southern Quebec (Canada). We sampled arthropods from sugar maples in 20 sugar maple–beech-dominated forest patches that varied in size and isolation from other forest patches. Within each patch, arthropods were collected in the interior, edge and canopy of patches over two seasons. Size and isolation of forest patches did not affect arthropod family or functional group diversity, but patch canopies supported a higher diversity than understories. Both configuration and within-patch location affected taxonomic and functional composition of arthropods. For example, phytophages and saprophages were found in greatest abundance in canopies and large patches, while entomophages were in highest abundance in interiors. We conclude that even in relatively small (e.g. 5–10 ha) forest patches, canopies are providing critical reservoirs for arthropod diversity, and draw our attention to the conservation value of small patches in fragmented forest landscapes.